Optimizing Employee Performance of the Central Statistics Agency through Transformational Leadership, Training: Job Satisfaction Mediators - Nuning Nurna Dewi; Rudi Wibowo (LPPM of NAROTAMA UNIVERSITY, 2026)
Performance is a real behavior displayed by each person as a perception of work by employees according to their role in the company. This study aims to determine the relationship between the influence of transformational leadership, job training, job satisfaction and employee performance of the Central Statistics Agency. This study uses a quantitative descriptive method. The sample and population are 37 employees. The data collection technique uses a Likert Scale. The data analysis method used in this study is Multiple Linear Regression Analysis, hypothesis testing and Path analysis with the help of the SPSS version 25 program. The results of the study show a positive and significant influence on the transformational leadership variable on employee performance of the Central Statistics Agency. There is a positive and significant influence on the job training variable on employee performance of the Central Statistics Agency. Transformational leadership has a positive and significant influence on Job Satisfaction of the Central Statistics Agency. Job training has a positive and significant influence on job satisfaction of the Central Statistics Agency. Job satisfaction has a positive and significant influence on employee performance of the Central Statistics Agency. Job satisfaction is able to mediate transformational leadership on employee performance of the Central Statistics Agency and job satisfaction is able to mediate job training on employee performance of the Central Statistics Agency.